Impact/influence of BRAC microfinance programme on fostering young entrepreneurship/rural women entrepreneurs: a focus/case study of "Progoti" programme one to one (individual loan)-microfinance of BRAC - Shahabuddin, Tahrima (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.